What should be prioritised in the development of an online intervention designed to support midwives in work-related psychological distress? An exploratory Delphi Survey. - Sally Pezaro (Frontiers Media S.A., 2015)
Background The need to improve the health and wellbeing of National Health Service (NHS) staff is becoming a key priority for healthcare leaders (England, 2014). Episodes of stress, anxiety and burnout are the most frequently cited reasons for staff absence, accounting for one quarter of all episodes of sickness absence in NHS staff (NHS Employers, 2014). The NHS workforce may be at an increased risk of psychological distress as a result of their demanding and relentless exposure to human suffering, workforce pressures and psychologically unsafe working cultures. This is of grave concern as poor NHS staff wellbeing has been shown to directly correlate with failing health care services (The Royal College of Physicians, 2015). When the NHS workforce suffers in poor health, this can lead to an increase in medical errors, infection rates, and mortality rates (Boorman, 2009; The Royal College of Physicians, 2015). This is not compatible with safe and effective patient care. Midwives have been known to experience high levels of death anxiety, post-traumatic stress disorder (PTSD), compassion fatigue, burnout and psychological distress (Rice & Warland, 2013; Sheen, Slade, & Spiby, 2014). However a recent situational analysis into clinician suicide has demonstrated that there is a paucity of support available to midwives in comparison to other professional groups (Strobl et al., 2014). Midwives are entitled to a psychologically safe professional journey as they strive to deliver high quality, safe care to mothers and babies. Therefore new and effective interventions are required to support midwives in work-related psychological distress. Aims Midwives have been known to suffer in silence, working in cultures which may prioritise self-sacrifice above self-care (Deery & Kirkham, 2006; Kirkham, 1999). Therefore, an online intervention may be one option midwives may turn to when in need of psychological support. The aim of this research will be to generate expert consensus on the needs of midwives in work-related psychological distress who may be supported via an online intervention. Methods A Delphi Study will invite over 120 experts in the fields of midwifery, psychology, psychiatry, therapeutic interventions and research to offer their opinion in what an online intervention designed to support midwives in work-related psychological distress should prioritise through 2 rounds of questioning. A preliminary round of inquiry will include 20 questions, which will allow experts to deliberate upon which ethical inclusions and inclusions of therapeutic support should be prioritised. Experts will also deliberate upon how the intervention should be designed, and which practical inclusions should be prioritised in its development. Participants will be asked to indicate their priority ratings via a 7 point Likert scale response. They will also be given the opportunity to elaborate upon their responses and ideas in relation to the development of the proposed online intervention, so that this study may evaluate both qualitative and quantitative outcomes. A thematic analysis of qualitative open responses will be presented in a table format and a feedback report of all results will be provided to panel members. Responses to the first round of questioning will inform the development of a second round of questioning where new questions may be formed as a result of new themes being identified. When 60% (≥18, assuming the minimum is 30) of panellists score within 2 adjacent points on a 7-point scale, consensus will be acknowledged. Items which do not achieve consensus in Round 1 will be re-presented in Round 2. Round 2 will consist of new questions, which will invite the same panel to once again indicate what may be prioritised in the development of an online intervention designed to support midwives in work-related psychological distress. These questions will address new themes identified within the first round of questioning, and will aim to generate firm consensus in any unresolved matters. The results of this second round of questioning will again be analysed thematically, and both qualitative and quantitative results will then be shared with the panel. A published protocol for this research outlines this methodology in further detail (Pezaro & Clyne, 2015). Results The results of this Delphi Study will inform the development and design of an online intervention designed to support midwives in work-related psychological distress. This study is currently in progress. The research team expects to collate and evaluate study outcomes during the autumn of 2015. Results will then be presented and published shortly afterwards. Conclusions This study outlines how consensus in the development of an online intervention designed to support midwives in work-related psychological distress may be achieved. Study outcomes will steer the design and development of an intervention, and highlight the most salient themes and elements to be included within an online intervention to support midwives. Midwives are entitled to psychological support, yet this is an area in which a paucity of knowledge in relation to their needs resides. This early research is the first of its kind to highlight the needs of midwives. Its' vision is to develop an evidence based solution to improve the health and well-being of midwives, as they, in turn, care for our mothers and babies.